Fuzzy Prime Ideals of ADL's - Chigurupalli Santhi Sundar Raj; Natnael Teshale Amare; Uppasetti Madana Swamy (LPPM Institut Teknologi Sepuluh Nopember, 2018)
In this paper the concept of prime L-fuzzy ideals and L-fuzzy prime ideals of an ADL A with truth values in a complete lattice L satisfying the infinite meet distributive law are introduced. All prime L-fuzzy ideals of a given ADL A are determined by establishing a one-to- one correspondence between prime L-fuzzy ideals of an ADL A and the pairs (P;a), where P is a prime ideal of A and a is a prime element in L. Also, here minimal prime L-fuzzy ideals and L-fuzzy minimal prime ideals of an ADL A are introduced and characterized.